Association of two variable number of tandem repeats in the monoamine oxidase A gene promoter with suicide completion: The present study and meta‐analysis - Masashi Hasegawa; Takaki Tanifuji; Satoshi Okazaki; Ikuo Otsuka; Toshiyuki Shirai; Ryota Shindo; Tadasu Horai; Kentaro Mouri; Motonori Takahashi; Takeshi Kondo; Yasuhiro Ueno; Akitoyo Hishimoto (Wiley, 2023)
Abstract Background One potential cause of suicide is serotonergic dysfunction. Sex differences have been reported to modulate the effects of serotonergic polymorphisms. Monoamine oxidase A (MAOA) is an enzyme that degrades serotonin and is located on the X chromosome. A previous study indicated that the upstream (u) variable number of tandem repeat (VNTR) in the MAOA gene promoter may be associated with suicide. However, a meta‐analysis showed that this polymorphism may not be related to suicide. According to a recent study, compared with the uVNTR, the distal (d)VNTR and the haplotypes of the two VNTRs modulate MAOA expression. Methods We examined the two VNTRs in the MAOA gene promoter in 1007 subjects who committed suicide and 844 healthy controls. We analyzed the two VNTRs using fluorescence‐based polymerase chain reaction assays. We conducted a meta‐analysis for the two VNTRs to update it. Results Our results demonstrated that neither the genotype‐based associations nor allele/haplotype frequencies of the two VNTRs were significantly associated with suicide. In the meta‐analysis, we did not indicate relationships between uVNTR and suicide nor did we identify articles analyzing dVNTR in suicide. Conclusion Overall, we did not find a relationship between the two VNTRs in the MAOA promoter and suicide completion; thus, warranting further studies are required.